Managing sustainable Boro rice production through bio-slurry practice in Mymensingh district of Bangladesh (Journal of the Bangladesh Agricultural University, 2017)
This study aimed to explore sustainable agricultural land management for Boro rice production through bio-slurry practice inBangladesh. Face to face interviews were used on bio-slurry user and non-user farmers in the selected areas of Mymensingh district. The nutritional values (Nitrogen (N), Phosphorus (P), and Potassium (K) of the slurry and non-slurry based soil were analyzed in the Department of Soil Science laboratory, BAU. Descriptive statistics were used to estimate the benefit and cost of boro rice production based on slurry and non-slurry practice. Likert Score scaling and Fishbein model were used to evaluate social acceptability and perception of slurry practices. Two-t sample test also applied for significance the difference of N,P, K on slurry based and non-slurry based soil.. Sixty households were purposively selected and the data were covered on socioeconomic characteristics, consumer attitude, income, cost, returns of bio-slurry and non-slurry based crop. The cost of N, P, K was reduced due to slurry practices instead of chemical fertilizer practices. The total production cost of boro rice per acre for slurry and non-slurry practices were BDT 31,064 and BDT 34,877 respectively, The per acre net return of bio-slurry and non-slurry based rice production were BDT 6056 and BDT 425 respectively and BCR were 1.19 and 1.01, respectively. The bio-slurry practice is much convenient for sustainable land management because it is economic viable, socially accepted and finally, slurry based soil contains significantly better Phosphorus and Potassium compared to non-slurry based soil.